Estimation of Critical Virtual Water for Irrigation to Avoid Crop Loss - Swathi Pai M., Prof.; Shalini, H; Aravinda C. V, Dr (International Journal of Engineering and Technology, 2018)
Most of the Indian population rely on agriculture forthe living. Its prosperity depends mainly on the weather parameters. Water assumes a noteworthy part in the growth of a crop. Occurrences of unpredictable weather are beyond human control. Due to which there are crop loss. Farmers fall into debts as they have to face a scarce crops productivity due to inadequate water supply and other climate conditions which increment the danger of their benefit and the high cost of living. Often, agriculturists may see the suicide as the main answer for their families. This paper presents an overview of the research on Estimation of Critical Virtual Water for Irrigation to Avoid Crop Loss. It is an endeavour to build up a prediction model to estimate the water utilized for irrigation with the "critical virtual water estimation" which would ensure the economic utilization of water in the state or the country. The Critical Virtual Water is the water estimation for the production of the particular crop. It takes into consideration the climate in the locality, measure of the water accessible in the region for farming and other agriculture factors. The analysis will be done for all the districts of the state Karnataka, India. Prediction model will advise the farmer about the best crop choice to be grown.Â Â